(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
Complex oxide compounds with a composition of LaBa6-xCu7Oy (0≤х≤2) have been obtained with sol-gel technique. The X-ray diffraction method was applied for characterization of the substituted complex cuprates and for calculation of parameters of their unit cell. Indexation of the spectra, estimation of the space group and crystallographic parameters were carried out using the INDEX and X-Ray programs. The calculation results showed that crystalline structure of the non-stoichiometric complex oxide is related to the space group of P4/mmm, the structure is characterized by following parameters: a = b = 0.39185(4) nm; c = 1.17385(2) nm; V = 0.18024(5) nm3 (RBregg = 5.0%; Rf = 4.91%). Diffuse reflection spectra were obtained for the samples. The values of reflection coefficient were found to increase with a growth of vacancy amount. All spectra contain the stripe caused by d-d transition of Cu2+ in octahedral coordination. Decrease of the х value results in a growth of the crystallite size. It should also note an inversely dependence of the grain size and reflection ability of surface of the complex cuprates. The dependence of specific electric resistance of the samples on temperature has been investigated. It was shown that the cuprate with a composition of LaBa5Cu7O14.15 is characterized by electronic conductivity in a wide temperature interval. Other samples demonstrate semi-conductive type of conductivity with small activation energy. The method of iodometric titration showed symbatically change of the amount of non-stoichiometric oxygen (δ) and average oxidation degree of copper (Сun+) with an increase of х. Thus, defects of the investigated cuprates are confirmed by iodometric titration.